Anatomy of Architecture Based on the Creation of Space for Activity - Salura, Purnama (International Journal of Engineering and Technology, 2018)
Currently, the research and analysis of the anatomy of architecture are very scarce to find, although this issue is very important to use to interpret the architectural artifact and also for designing architecture. If a researcher or designer understands correctly about the anatomy of architecture, then the results will increase the value of the natural environment and the value of the human environment. This research is a theoretical research that raised the issue of the anatomy of architecture. The purpose of this study was to fully reveal all aspects that affected the anatomy of architecture and then put forward a new anatomy of architecture. In this study, two important theories of architecture made as a case study. These two theories analyzed, compared and elaborated in-depth. This research succeeded in compiling a new anatomy of architecture concept which departed from space created and its context. The results of this study are used as a reference for interpreting architectural artifacts as well as guides to designing architecture. Another benefit is to fill the scarcity of existing literature on the anatomy of architectural issues.Â Â